Halomonas levan-coated phospholipid based nano-carrier for active targeting of A549 lung cancer cells - EROĞLU, MEHMET SAYIP; SENNAROĞLU BOSTAN, MÜGE (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Novel core-shell structured nano-particles (NP) were developed, applying a new strategy to deliver paclitaxel (PTX) to human lung A549 cancer cells. PTX loaded and ionically cross-linked lipidic nanoparticles (PTX-LNPs), having negative surface charges, were coated with low molecular weight quaternized Halomonas levan (QHL) through Coulomb interaction. Chemical modification of Halomonas levan (HL) was performed using glycidyl trimethyl ammonium chloride (GTMAC) as a quaternizing agent to generate positive charges. Fluorescein sodium salt was inserted into the core-shell interface to monitor the internalization of NPs. The average particle size of the NPs was determined to be 208 nm by dynamic light scattering measurement (DLS). Coating of the lipidic nanoparticles (LNPs) with QHL significantly altered the surface charge as the zeta potential changed from -75 mV to -0.85 mV, indicating successful covering of the LNPs with QHL. PTX anticancer drug was successfully loaded into the nanoparticles. Comparative PTX release profiles of PTX-LNPs and QHL-coated PTX-LNPs (QHL-PTX-LNPs) indicated that QHL shell prevented the burst release of PTX for six hours, maintaining a prolonged period of time for drug delivery. Fluorescence microscopy images showed a high level of internalization of the core-shell structured NPs into human lung A549 cancer cells, for which in vitro cell studies indicated that QHL-PTX-LNPs are more preferred. They showed higher cyctotoxicity compared to uncoated PTX-LNPs within 72 h. These results revealed that QHL-PTX-LNPs have a promising therapeutic effect for actively targeting human lung cancer cells.
Keywords: Levan; Lipidic NPs; Paclitaxel; Cancer targeting; Nanoparticle; DRUG-DELIVERY; HYALURONIC-ACID; LIPOSOMAL DOXORUBICIN; HYBRID NANOPARTICLES; ANTITUMOR-ACTIVITY; MOLECULAR-WEIGHT; SMYRNENSIS; MUCOADHESION; PACLITAXEL; KINETICS